2007
DOI: 10.1172/jci31097
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-mediated innate immune resistance to mycobacteria

Abstract: Neutrophils contain antimicrobial peptides with antituberculous activity, but their contribution to immune resistance to tuberculosis (TB) infection has not been previously investigated to our knowledge. We determined differential white cell counts in peripheral blood of 189 adults who had come into contact with patients diagnosed with active TB in London, United Kingdom, and evaluated them for evidence of TB infection and capacity to restrict mycobacterial growth in whole-blood assays. Risk of TB infection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
215
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 350 publications
(232 citation statements)
references
References 33 publications
10
215
3
4
Order By: Relevance
“…Although the role of neutrophils in protection and pathogenesis in TB remains controversial, these effector cells clearly contribute to inflammation in acute TB [95,96]. The involvement of neutrophil-mediated lung injury could participate in the formation of necrotic and caseous granulomas [97].…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of neutrophils in protection and pathogenesis in TB remains controversial, these effector cells clearly contribute to inflammation in acute TB [95,96]. The involvement of neutrophil-mediated lung injury could participate in the formation of necrotic and caseous granulomas [97].…”
Section: Resultsmentioning
confidence: 99%
“…This organism has been very well-characterized and utilized in a wide range of clinical and non-clinical studies [21,24,2732,51]. For example, differences in M. bovis BCG lux RLU measurements have been shown to reflect changes in the immune response in human whole blood and cellular models, including differences between tuberculin-positive and -negative individuals [23], changes induced by HIV infection and following antiretroviral treatment [25,26], changes in mycobacterial growth limitation induced by vaccines [24] and Vitamin D supplementation in vitro and in a clinical trial [2931], and differences in gene expression in immune biological pathways compared to M. tuberculosis [32]. In addition we have also evaluated luminescent mycobacteria in the mouse model [27].…”
Section: Discussionmentioning
confidence: 99%
“…32 We and others have also previously demonstrated that 1a,25(OH) 2 D 3 induces the antimicrobial peptide cathelicidin LL-37, which possesses antituberculous activity. 22,33,34 PBMC + EtOH This report describes a complementary mechanism whereby vitamin D could exert a beneficial effect on host response to M. tuberculosis by inhibiting the expression, secretion and activity of a number of MMP induced by M. tuberculosis, consequently limiting the degradation of extracellular matrix and decreasing pulmonary cavitation to preserve lung function and reduce infectiousness.…”
Section: Discussionmentioning
confidence: 99%